Kinetics study of activated carbons and carbon dioxide systems - Gan, You Loo (2013)
In this project, we will look into the physical gas adsorptions between carbon dioxide with Maxsorb III. The experiment was carried out at constant temperature and fitted with various isotherm models. The experimental apparatus and procedures followed largely those of previous research. However, some modifications were made in order to obtain better results.